(untitled) (Bangladesh Journal of Botany, 2025)
The investigation conducted an analysis of 23 cherry tomato genotypes, examining 19 qualitative and quantitative traits related to plants, flowers, fruits, and seeds. A wide spectrum of variability was observed among the cherry tomato genotypes. The correlation coefficients unveiled significant positive and negative relationships between various traits, particularly emphasizing flowering time, fruit quality, and biochemical characteristics. The evaluation through path coefficient analysis pinpointed essential factors that affect fruit yield per plot, highlighting traits such as stem girth, number of fruits per cluster, pericarp thickness and shelf-life. PCA indicated that both quantitative and qualitative morphological parameters captured a substantial amount of variability. The hierarchical cluster analysis categorized the genotypes into groups, suggesting opportunities for breeding for different objectives. The dendrogram illustrated differences and similarities in traits among cherry tomato genotypes. Therefore, selection based on these traits could be effective for higher yield in cherry tomato genotypes. Bangladesh J. Bot. 54(1): 105-111, 2025 (March)